DISTRIBUTION AND EXPRESSION OF STRIPED CATFISH (Pangasionodon hypophtalmus) GROWTH HORMONE GENE (PhGH) IN THE ORGAN OF AFRICAN CATFISH (Clarias gariepinus) TRANSGENIC FOUNDER - Huria Marnis; Raden Roro Sri Pudji Sinarni Dewi; Imron Imron; Bambang Iswanto (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2012)
Faster growing African catfish can be produced by transgenesis. This study was conducted to investigate the distribution and expression of growth hormone gene (PhGH) in various organs of the transgenic African catfish (Clarias gariepinus) founder (F0). Transgene was detected using the PCR method in various organs, namely pituitary, brain, liver, heart, spleen, kidney, intestine, stomach, muscle, caudal fin, gill and eye. Transgene expression levels were analyzed using the method of reverse transcriptase-polymerase chain reaction (RT-PCR), -actin gene used as internal controls. The results showed that the PhGH was detected and expressed in all organs of the transgenic African catfish founder. The high level of PhGH expression was found in the liver, pituitary, intestine and brain; smaller amounts were detectable in muscle, spleen, kidneys, heart, and stomach, caudal fin, gill and eyes, range from 0.02-0.75 PhGH/-actin mRNA. The expression levels of PhGH had positive correlation with tissue and body size (P<0.05).